Telekom Malaysia Berhad a study on customer satisfaction through door to door sales activity / Zuraini Ismail - Ismail, Zuraini (2000)
A very stiff competition is taking place among the telecommunication operator in our country, as telecommunication industry is a competitive business. Since the growing in telecommunication industry, Telekom Malaysia Berhad is becoming the major telecommunication provider in our country. But, due to the highly competition from other operators, Telekom is implementing another strategy promotion in order to maintain the position in this industry. Beside that, the major goal of service provider is to give satisfaction to all their customers. This research project is carried out to examine the customer satisfaction through one of strategy promotion that implementing by Telekom, which is door to door sales activity.